Evaluation of cellular antioxidant activity of selected species of Caralluma and Boucerosia on cell lines - Vajha, Madhuri; Chillara, Siva Rama Krishna (International Journal of Applied Sciences and Biotechnology, 2014)
Objective: The aim of the present work was designed to study cellular antioxidant properties of selected plant extracts of Caralluma and Boucerosia on cell lines. Materials and Methods: The present study was carried out in four species of Caralluma R.Br. such as Caralluma adscendens (Roxb.) R. Brown var. attenuata (Wight) Grav. & Mayur. (CAA), Caralluma adscendens (Roxb.) R. Brown var. fimbriata (Wall.) Gravely & Mayur. (CAF), Caralluma stalagmifera C.E.C. Fisch. (CS) and Caralluma stalagmifera C.E.C. Fisch. var. longipetala Karupp. & Pull. (CSL) and as well as two species of Boucerosia Wight & Arn. such as Boucerosia lasiantha Wight. (BL) and Boucerosia umbellata (Haw.) Wight & Arn. (BU). The antioxidant efficacy was evaluated by ability of antioxidant molecules in the extract to scavenge ROS produced by normal metabolism by cells, observed by the oxidation of 2, 7- Dichloro fluorescein diacetate to dichlorofluorescein, followed by decrease in fluorescence intensity. Results: Cellular antioxidant activity was demonstrated by the inhibitory concentration 50% (IC50) of reactive oxygen species (ROS). The percentage ROS inhibition in Raw 264.7 cells when treated with different concentrations of methanolic extracts showed variations among selected species. Conclusion: The plant extracts were shown to be effective for antioxidant potential and can be a promising source of natural antioxidants. DOI: http://dx.doi.org/10.3126/ijasbt.v2i1.9649 Int J Appl Sci Biotechnol, Vol. 2(1): 83-87